Effects of ozone treatment on the antioxidant capacity of postharvest strawberry. Issue 63 (15th October 2020) - Zhang, Huijie; Li, Kunlun; Zhang, Xiaojun; Dong, Chenghu; Ji, Haipeng; Ke, Runhui; Ban, Zhaojun; Hu, Yunfeng; Lin, Shaohua; Chen, Cunkun
Abstract : Strawberries are highly popular around the world because of their juicy flesh and unique taste. Abstract : Strawberries are highly popular around the world because of their juicy flesh and unique taste. However, they are delicate and extremely susceptible to peroxidation of their membrane lipids during storage, which induces water loss and rotting of the fruit. This study investigated the effects of ozone treatment on the physiological traits, active oxygen metabolism, and the antioxidant properties of postharvest strawberry. The results revealed that the weight loss (WL) and respiration rate (RR) of strawberry were inhibited by ozone treatment (OT), while the decline of firmness (FIR) and total soluble solids (TSS) were delayed. Ozone also reduced the generation rate of superoxide radical anions, and the content of hydrogen peroxide (H2 O2 ) enhanced the activity of superoxidase (SOD), catalase (CAT), ascorbate peroxidase (APX), and monodehydroascorbate reductase (MDHAR), as well as promoted the accumulation of ascorbic acid (ASA), glutathione (GSH), and ferric reducing/antioxidant power (FRAP). In addition, a total of 29 antioxidant-related proteins were changed between the OT group and control (CK) group as detected by label-free proteomics during the storage time, and the abundance associated with ASA–GSH cycle was higher in the OT group at the later stage of storage, and the qRT-PCR results were consistent with those of proteomics. The improvement of the antioxidant capacity of postharvest strawberry treated with ozone may be achieved by enhancing the activity of the antioxidant enzymes and increasing the expression of the antioxidant proteins related to the ascorbic acid–glutathione (ASA–GSH) cycle.